PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA HOTEL RESTY MENARA PEKANBARU - Melati Claudia; Dewita Suryati Ningsih; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The population and samples in this study is all employee about 75 people. The data recourses used were primary and secondary data. The data accumulation technique used were taken by doing interview and questionnaire. The method of analysis used were the method of quantitative descritive and multiple regression analysis (simultaneously and partially analysis) with the help of SPSS 17 version. Based on the results of multiple regression analysis, simultaneously test showed that motivation (X1) and discipline (X2) had a significant effect on labor performance (Y). The influence of each independent variables on dependent variable could be seen by doing partial test, the results showed that motivation (X1) and discipline (X2) had a significant effect on labor performance (Y). And for that, writer suggested for the company to watch another factors that can influence on labor performance, because the company and the labor are both work partner that needed each other for the welfare of the company.Keywords: motivation, discipline, and labor performance.